2001
DOI: 10.1128/aem.67.5.2304-2309.2001
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Stress-Induced Neuroendocrine Changes Increase the Susceptibility of Juvenile Oysters ( Crassostrea gigas ) to Vibrio splendidus

Abstract: Oysters are permanently exposed to various microbes, and their defense system is continuously solicited to prevent accumulation of invading and pathogenic organisms. Therefore, impairment of the animal's defense system usually results in mass mortalities in cultured oyster stocks or increased bacterial loads in food products intended for human consumption. In the present study, experiments were conducted to examine the effects of stress on the juvenile oyster's resistance to the oyster pathogen Vibrio splendid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 20 publications
2
76
0
1
Order By: Relevance
“…Mycoplasmas can be potent respiratory pathogens of ruminants, and recently O'Neal et al used microarray analysis to show that gene expression in Mycoplasma hyponeumoniae underwent substantial changes when exposed to NA, including up-regulation of genes encoding host tissue attachment factors (O 'Neal et al, 2008). Stress hormone enhancement of growth and virulence is not solely a feature of pathogens of mammalian hosts, as it has been demonstrated that norepinephrine can increase the infectivity of bacteria causing infections in non-vertebrates species such as oysters (Vibrio species) (Lacoste et al, 2001) and amphibians such as frogs (Aeromonas hydrophila; Kinney et al, 1999).…”
Section: Microbial Endocrinologymentioning
confidence: 99%
“…Mycoplasmas can be potent respiratory pathogens of ruminants, and recently O'Neal et al used microarray analysis to show that gene expression in Mycoplasma hyponeumoniae underwent substantial changes when exposed to NA, including up-regulation of genes encoding host tissue attachment factors (O 'Neal et al, 2008). Stress hormone enhancement of growth and virulence is not solely a feature of pathogens of mammalian hosts, as it has been demonstrated that norepinephrine can increase the infectivity of bacteria causing infections in non-vertebrates species such as oysters (Vibrio species) (Lacoste et al, 2001) and amphibians such as frogs (Aeromonas hydrophila; Kinney et al, 1999).…”
Section: Microbial Endocrinologymentioning
confidence: 99%
“…Microbial Endocrinology concepts can even be extended to non-vertebrates. Lacoste et al showed that stressing farmed oysters led to increased susceptibility to infection with Vibrio species that was directly linked to increased production of noradrenaline in the shell fish; the injection of noradrenaline into unstressed oysters also significantly increased oyster mortality to subsequent Vibrio infection [20].…”
Section: The Spectrum Of Stress Hormone Responsive Microbesmentioning
confidence: 99%
“…Dopamine is produced in a subpopulation of non-sympathetic enteric neurons located within the intestinal wall [8]. Table 1 [ [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] shows the microbes responsive to catecholamine stress hormones. What is most apparent is that the spectrum of hormone responsive microbes is weighted towards bacteria inhabiting the gastrointestinal tract, particularly species such as Escherichia coli, Salmonella, Listeria, Campylobacter, and Yersinia [9, 12,13,[15][16][17][18]22].…”
Section: The Spectrum Of Stress Hormone Responsive Microbesmentioning
confidence: 99%
“…As with other filter-feeding marine bivalves, oysters can accumulate large numbers of viruses, such as hepatitis A virus, and bacteria, such as Vibrio cholerae, Vibrio vulnificus, and Vibrio parahaemolyticus, when they are present in the surrounding water (16,25,49,53) and may act as passive carriers of human pathogens (14). To help defend themselves against viral and microbial infections, oysters have efficient cellular and humoral immune defense mechanisms (14,36). However, poor water quality can impair some of these mechanisms, thereby increasing the risk that oysters will harbor and transmit pathogens that are harmful to humans, oysters, and the environment (8,10,16,23,33,36,49).…”
mentioning
confidence: 99%